1999
DOI: 10.1083/jcb.146.4.819
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo, Villin Is Required for Ca2+-Dependent F-Actin Disruption in Intestinal Brush Borders

Abstract: Villin is an actin-binding protein localized in intestinal and kidney brush borders. In vitro, villin has been demonstrated to bundle and sever F-actin in a Ca2+-dependent manner. We generated knockout mice to study the role of villin in vivo. In villin-null mice, no noticeable changes were observed in the ultrastructure of the microvilli or in the localization and expression of the actin-binding and membrane proteins of the intestine. Interestingly, the response to elevated intracellular Ca2+ differed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
166
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(174 citation statements)
references
References 50 publications
6
166
1
1
Order By: Relevance
“…These data agree with the observations in UC patients that increasing rates of colonic epithelial apoptosis correlate with increasing severity of the disease (11). Our study also potentially provides an explanation for the higher death probability noted previously in DSS-treated villin knock-out mice compared with their wild-type littermates (24). No differences in the expression of brush border or tight junction proteins have been noted in the villin-null mice (24,25).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…These data agree with the observations in UC patients that increasing rates of colonic epithelial apoptosis correlate with increasing severity of the disease (11). Our study also potentially provides an explanation for the higher death probability noted previously in DSS-treated villin knock-out mice compared with their wild-type littermates (24). No differences in the expression of brush border or tight junction proteins have been noted in the villin-null mice (24,25).…”
Section: Discussionmentioning
confidence: 50%
“…Our study also potentially provides an explanation for the higher death probability noted previously in DSS-treated villin knock-out mice compared with their wild-type littermates (24). No differences in the expression of brush border or tight junction proteins have been noted in the villin-null mice (24,25). No significant changes in the other actin-binding proteins were noted either (24,25).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It has been assumed for several years that villin's actin-bundling and not actin-severing functions are important because nonphysiologically high Ca 2ϩ concentrations (200 M) are required to activate villin's actin-severing activity. However, studies done with the villin knockout mice suggest that in the absence of villin, the actin-bundling properties associated with villin can be substituted by other proteins in the microvilli (Pinson et al, 1998); on the other hand, the actin-severing activity of the microvilli is lost (Ferrary et al, 1999). In recent years, we have demonstrated that villin's actin-modifying functions can be regulated in vitro by tyrosine phosphorylation and phosphatidylinositol bisphosphate (PIP 2 ), suggesting that villin has the potential to function as a link between receptor activation and actin cytoskeleton reorganization even in the absence of high calcium (Arora and McCulloch, 1996;Zhai et al, 2001;.…”
mentioning
confidence: 99%